PENYULUHAN DAN PENANAMAN BIBIT-BIBIT DURIAN PADA LAHAN KRITIS DI DESA CURUG, KOTA BOGOR - Fathaddin, Muhammad Taufiq; Safitri, Diah Utami; Prapansya, Onnie Ridaliani; Marwanza, Irfan; Nuryana, Suherman Dwi; Pramadika, Havidh; Maulida, Fajri; Arkaan, Muhammad Dzaki (Universitas Trisakti, 2024)
The region in Indonesia is indicated to have many critical lands. Critical lands are lands that have experienced degradation so that the land cannot function properly. In other words, efforts to obtain benefits from the level of productivity that should not be comparable to the results of production. Therefore, efforts must be made to improve the land so that its productivity can recover. In the Curug sub-district, Bogor City, there are critical lands. This critical land is caused by steep land topology and high rainfall. One of the critical land areas is the Curug River watershed. The slope of the land on the side of the river exceeds a slope of 45º. High rainfall causes the land to experience cracks accompanied by subsidence of the land surface. One of the handling efforts that can be carried out on an ongoing basis is integrated reforestation. Based on these problems, the aim of this community service (PKM) is to provide education regarding the dangers of critical land and cultivating critical land with durian seeds. This activity was carried out by a team consisting of source persons, lecturers and students from the Faculty of Earth and Energy Technology, Trisakti University. The PKM activity was attended by the Head of RW 13 and the Head of RT 3 in Curug Village and their staff. Apart from that, the PKM was attended by the men and women of RT 3 residents who actively participated in counseling activities and planting durian seeds along the areas along the river and other areas.